Efeito de sorgo com alto teor de lisina no crescimento de ratos - Maffia, Lúcia Maria; Batista , Cid M; Meira, José Lydio (Revista Ceres, 2025)
Research was conducted to evaluate the protein quality of two varieties of sorghum (Sorghum halipensis Pers.) — common sorghum and a high lysine variety — as compared with millet (Pennisetum typhoideum Rich.) and casein. Data on food consumption, nitrogen intake, body weight and protein efficiency ratio (PER) were obtained from weanling rats.